O2 Deficiency of the mitochondrial hydrogen sulfide clearance enzyme thiosulfate sulfurtransferase ameliorates atherosclerosis in Apoe-knockout mice. (May 2019) - Bléhaut, Tanguy RW; Gibbins, Matthew TG; Horvat, Simon; Hadoke, Patrick WF; Morton, Nicholas M
Abstract : Background: Hydrogen sulfide (H2 S) is an atheroprotective gaseous signalling molecule. The atheroprotective properties of H2 S are in part mediated through the endothelium and the nitric oxide pathway. We studied a novel target for H2 S bioavailability, and therefore atherosclerosis, the enzyme thiosulfate sulfurtransferase (TST; which catalyses mitochondrial H2 S clearance), using Apoe –/– mice (an established atherosclerosis model) lacking the gene for TST ( Apoe –/– Tst –/– mice). We hypothesized that lack of TST would protect against the development of atherosclerotic plaque through preservation of endothelial cell function. Methods: Plaque quantification: 4-week-old, male, Apoe –/– Tst –/– mice (n=9) and Apoe –/– control mice (n=9) were fed a Western diet (42% (kcal) fat and 0.15% (w/w) cholesterol) for 12 weeks. Plaque volume within the brachiocephalic trunk was measured ex vivo using optical projection tomography (OPT) and average plaque cross-sectional area was measured with conventional histology. Endothelial function studies: 11–12 week old, male, Apoe –/– Tst –/– mice (n=6) and Apoe –/– control mice (n=8) were fed a Western diet for 16 weeks. Functional responses of intact and denuded rings of thoracic aorta were measured in response to vasoconstrictors (phenylephrine, 5-hydroxytryptamine), and endothelium-dependent (acetylcholine) and -independent (sodium nitroprusside) vasodilators. Results: Apoe –/– Tst –/– mice had significantly smaller plaque volume ( Apoe –/– Tst –/–, 8.12 x 10 7 ±1.51 x 10 7 µm 3 ; Apoe –/–, 1.22 x 10 8 ±1.14 x10 7 µm 3 ; p=0.048), and lower average plaque cross-sectional area ( Apoe –/– Tst –/–, 1.50 x 10 5 ±3.09 x 10 4 pixels; Apoe –/–, 2.72 x 10 5 ±3.39 x 10 4 pixels; p=0.018) compared to Apoe –/– controls. Functional responses to vasoconstrictor and vasorelaxant compounds were similar in Apoe –/– Tst –/– and Apoe –/– mice. Unexpectedly, there was no evidence of endothelial dysfunction in these animals. Conclusions: These results demonstrate that deletion of Tst reduces lesion size in a mouse model of atherosclerosis. Functional investigations suggest that this is not the result of improved endothelial cell function. Further experiments will determine whether reduced lesion size is due to the reduction in particular components of the lesion. This work suggests that TST has potential as a therapeutic target in atherosclerosis.